Mapping Colonial Archives as Counter-Practice - Denieul-Pinsky, Léa (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
This paper explores how mapping projects sourced directly from institutional and colonial archival collections can provide interesting avenues of research for Indigenous communities confronted with historical erasure. New counter-archival practices are emerging using cartography to defy government institutions using their own materials. To illustrate this point, I begin by tracing the initial emergence of counter-archives and counter-maps as separate fields and their current joint mobilization. This leads me to argue that colonial archives deserve to be considered for counter mapping practices. Then, I interview researchers, Ana Pulido Rull, Margaret Pearce, Tristan Ahtone and Robert Lee, who have repurposed state-sponsored colonial archives as primary source materials in their counter-mapping projects. Our conversations reveal that colonial land grant maps, registries and land patent records are highly versatile. When recombined creatively, they can offer valuable insights for understanding and reclaiming lands that were taken through settler colonial policies. Spatial analysis can help piece together fragmented narratives by interconnecting individual records and situating them within the territory they claim to represent. This is promising, but leveraging archival materials for meaningful impact requires methodological care. Documenting the mapping process is crucial for understanding how fragmented data is reused to generate specific analyses. Failing to do so risks perpetuating the same power dynamics and harmful narratives present in the original records.